Histone Deacetylase 2 Is a Component of Influenza A Virus-Induced Host Antiviral Response - Nagesh, Prashanth T.; Hussain, Mazhar; Galvin, Henry D.; Husain, Matloob (Frontiers in Microbiology, 2017)
Host cells produce variety of antiviral factors that create an antiviral state and target various stages of influenza A virus (IAV) life cycle to inhibit infection. However, IAV has evolved various strategies to antagonize those antiviral factors. Recently, we reported that a member of class I host histone deacetylases (HDACs), HDAC1 possesses an anti-IAV function. Herein, we provide evidence that HDAC2, another class I member and closely-related to HDAC1 in structure and function, also possesses anti-IAV properties. In turn, IAV, like HDAC1, dysregulates HDAC2, mainly at the polypeptide level through proteasomal degradation to potentially minimize its antiviral effect. We found that IAV downregulated the HDAC2 polypeptide level in A549 cells in an H1N1 strain-independent manner by up to 47%, which was recovered to almost 100% level in the presence of proteasome-inhibitor MG132. A further knockdown in HDAC2 expression by up to 90% via RNA interference augmented the growth kinetics of IAV in A549 cells by more than 4-fold after 24 h of infection. Furthermore, the knockdown of HDAC2 expression decreased the IAV-induced phosphorylation of the transcription factor, Signal Transducer and Activator of Transcription I (STAT1) and the expression of interferon-stimulated gene, viperin in infected cells by 41% and 53%, respectively. The role of HDAC2 in viperin expression was analogous to that of HDAC1, but it was not in the phosphorylation of STAT1. This indicated that, like HDAC1, HDAC2 is a component of IAV-induced host innate antiviral response and performs both redundant and non-redundant functions vis-a-vis HDAC1; however, IAV dysregulates them both in a redundant manner.